Marketing Cost and Price Spread of Rose Flower in Karnataka - A case study - Savadatti, Pushpa M.; Muddi, Mrunalini K. (Indian Journal of Marketing, 2006)
Over the years, horticulture has emerged as an important part of agriculture, offering wide range of choice to the farmers for crop diversification. Horticulture contributes about 24.5 percent of the Gross Domestic Product from about 8 percent of the area (Shikamany and Sudha, 2004). Floriculture, which is an integral part of horticulture, is growing at a much faster rate. Though the art of growing flowers is not new to India, large-scale commercial cultivation is of recent origin. In the world of marketing, Indian floriculture industry is witnessing an unprecedented growth and increasing acceptability. The floriculture industry is growing at a rate of 17 per cent per annum. Higher standards of living and a growing desire to live in an environment friendly atmosphere have led to an increasing demand for floriculture in India. The export of cut flowers has been identified as a thrust area at the national level.